Pengaruh Model Discovery Learning Berbantuan Geogebra terhadap Kemampuan Pemahaman Konsep Matematis Siswa di SMP Negeri 3 Tanjung Morawa - Mifta Aqila Nasution; Izwita Dewi (Journal on Education, 2024)
This research is a quasi-experimental research. The objectives of this study are to: (1) determine the influence on the use of the geogebra-assisted Discovery Learning model on students' ability to understand mathematical concepts, (2) know the influence of KAM on students' ability to understand mathematical concepts, (3) know the interaction between geogebra-assisted discovery learning models and KAM on students' mathematical concept understanding ability, (4) find out how much influence on the use of geogebra-assisted Discovery Learning models to the ability to understand mathematical concepts of students. The instrument used is a test of the ability to understand mathematical concepts. The results of this study show that: (1) Geogebra-assisted discovery learning model has a significant effect on students' ability to understand mathematical concepts, (2) Students' initial mathematical ability has a significant effect on students' ability to understand mathematical concepts, (3) there is no interaction between the geogebra-assisted discovery learning learning model and KAM on students' ability to understand mathematical concepts, (4) the geogebra-assisted discovery learning model has an influence of 87.8% on students' ability to understand mathematical concepts in experimental classes and the other 12.2% is influenced by other factors that affect students' abilities.